2016
DOI: 10.1117/12.2211608
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative label-free sperm imaging by means of transport of intensity

Abstract: Most living cells are optically transparent which makes it difficult to visualize them under bright field microscopy. Use of contrast agents or markers and staining procedures are often followed to observe these cells. However, most of these staining agents are toxic and not applicable for live cell imaging. In the last decade, quantitative phase imaging has become an indispensable tool for morphological characterization of the phase objects without any markers. In this paper, we report noninterferometric quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For dataset preparation, TIE is being used for creating phase and intensity image pair 39 . In optical and electron microscopy, the TIE is a computational method for reconstructing the phase of a complex wave 40 . One of the main bottlenecks for DL algorithms is that it requires a large dataset, i.e., images for proper training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For dataset preparation, TIE is being used for creating phase and intensity image pair 39 . In optical and electron microscopy, the TIE is a computational method for reconstructing the phase of a complex wave 40 . One of the main bottlenecks for DL algorithms is that it requires a large dataset, i.e., images for proper training.…”
Section: Introductionmentioning
confidence: 99%
“… 39 In optical and electron microscopy, the TIE is a computational method for reconstructing the phase of a complex wave. 40 One of the main bottlenecks for DL algorithms is that it requires a large dataset, i.e., images for proper training. Hence, during the experiments our focus was to generate an appropriate number of images for training the neural network.…”
Section: Introductionmentioning
confidence: 99%
“…9 Various implementations of QPI have been used recently to study the topography of gametes, assuming a certain refractive index. [10][11][12][13][14][15][16] Rappaz et al 17 reported an experimental procedure to calculate both the refractive index and the cellular thickness from the phase shift using digital holographic microscopy. The method relied on imaging the same cell in two solutions of different refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…QPI is an emerging method that provides quantitative information about transparent specimens, with nanoscale sensitivity and in label-free mode 9 . Various implementations of QPI have been used recently to study the topography of gametes, assuming a certain refractive index [10][11][12][13][14][15][16] . Here, for the first-time to our knowledge, we measure independently the thickness and refractive index of the cells.…”
mentioning
confidence: 99%